A cadmium sulfide nanorod, a cadmium sulfide nanorod composite coating plate, and a preparation method and application thereof
Patent Information
- Application Number
- CN202610505635.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-16
AI Technical Summary
当游离酸浓度超过工艺阈值(通常以总酸度与游离酸度比值表征)时,会显著影响磷化膜的成膜动力学过程,具体表现为膜层生长速率减缓、结晶颗粒粗化,严重时将引发已形成的磷酸锌膜层发生溶解反应,导致膜层完整性与防护性能下降
本发明基于复配形貌控制剂制备的硫化镉纳米棒物相纯度高、结晶度好,具有纳米棒状结构、分散性好,有利于暴露更多活性位点,提高光催化性能;
Smart Images

Figure CN122403490B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalysis and electrolytic phosphating technology, specifically relating to a cadmium sulfide nanorod, a cadmium sulfide nanorod composite coated electrode plate, its preparation method and application. Background Technology
[0002] Electrolytic phosphating, as a novel surface treatment technology, differs significantly from traditional impregnation phosphating processes. Its core advantage lies in its unique film-forming mechanism driven by electrochemical reactions, achieving slag-free phosphating. The basic principle of this process involves immersing the steel wire substrate and an inert electrode plate together in a specifically formulated electrolytic phosphating working solution, forming a complete electrolytic cell system via an external DC power supply. In this system, the steel wire substrate serves as the cathode, while an inert conductor material (such as a titanium-coated electrode) acts as the anode, forming a stable electrode pair. In the anode region (i.e., the surface of the inert electrode plate), water molecules undergo an oxidation reaction (oxygen evolution reaction): 2H₂O - 4e⁻. - →O2↑+4H + The reaction continuously releases hydrogen ions into the working fluid, accompanied by oxygen bubbles escaping from the electrode surface. Simultaneously, a reduction reaction (hydrogen evolution reaction) occurs in the cathode region (surface of the steel wire substrate): 2H₂O + +2e - →H2↑, this process continuously consumes hydrogen ions in the working fluid and generates hydrogen gas. Driven by the electrochemical reaction, dihydrogen phosphate ions at the steel wire substrate interface lose protons due to the change in hydrogen ion concentration gradient, and react with metal cations in the solution (mainly Zn). 2+ These substances combine to form zinc phosphate ortho-salts. These salts then undergo orderly crystallization and dense packing on the surface of the steel wire through directional diffusion, ultimately forming an electrolytic phosphating film with a uniform structure and good adhesion.
[0003] In the dynamic process of electrolytic phosphating, paired reactions of hydrogen release and oxygen generation occur at the cathode and anode, respectively, forming the core cycle of the entire electrochemical reaction. It is noteworthy that, in addition to the dominant hydrogen evolution reaction at the cathode interface, due to the combined effects of electrode polarization and hydrogen overpotential, zinc ions in the solution gain electrons at the cathode surface and undergo a reduction reaction: Zn 2+ +2e - →Zn, forming elemental zinc. This side reaction results in the electrolytic phosphating film having a chemical composition of a composite system of zinc phosphate and elemental zinc, which co-deposit within the film structure. Simultaneously, as the hydrogen evolution reaction at the cathode continues, the phosphate molecules in the phosphating solution are affected by the electrochemical environment, and their three-step ionization equilibrium ( All free ions move towards ionization, causing the concentration of free hydrogen ions (i.e., free acid content) in the bath solution to gradually increase. When the free acid concentration exceeds the process threshold (usually characterized by the ratio of total acidity to free acidity), it will significantly affect the film formation kinetics of the phosphating film. Specifically, this manifests as a slowdown in film growth rate and coarsening of crystal particles. In severe cases, it will trigger a dissolution reaction in the already formed zinc phosphate film, leading to a decrease in film integrity and protective performance.
[0004] Semiconductor photocatalysts are commonly used for photohydrolysis to produce hydrogen or for the degradation of organic pollutants, but they have not yet been used in electrolytic phosphating processes to reduce the concentration of free hydrogen ions (i.e., free acid content).
[0005] Therefore, developing a method based on semiconductor photocatalysts to reduce the concentration of free hydrogen ions and improve the electrolytic phosphating effect has important application prospects. Summary of the Invention
[0006] To overcome the shortcomings of the prior art, the present invention provides a cadmium sulfide nanorod, a cadmium sulfide nanorod composite coated electrode plate, its preparation method and application.
[0007] The cadmium sulfide nanorods of this invention exhibit photocatalytic effects, consuming excess H₂ in the system through an electronic transition and redox coupling mechanism of a semiconductor photocatalyst. + Furthermore, the introduction of a sacrificial agent can further optimize photocatalytic efficiency. The specific principle is as follows: Generation of photogenerated carriers: When irradiated with photons of energy higher than the band gap of a semiconductor photocatalyst, electrons in the valence band (VB) of the catalyst are excited to the conduction band (CB), forming photogenerated electrons (e) with strong reducing properties. - ) and oxidative valence band holes (h + This provides a basis for subsequent redox reactions.
[0008] Hole consumption and hydrogen ion removal: Direct reaction pathway: Holes can directly oxidize water molecules or hydroxyl groups (OH-) adsorbed on the catalyst surface. - ), generating strong oxidizing hydroxyl radicals ( OH), the reaction formula is: h + +H2O→ OH+H + Simultaneously, photogenerated electrons can directly capture H+ in the solution through surface defect sites. + A reduction reaction occurs to produce H2, consuming free hydrogen ions. The reaction equation is: 2H2O + +2e - →H2↑.
[0009] Sacrificial agent-assisted pathway: Adding a sacrificial agent (such as alcohols, organic acids, thiosulfates, and other reducing substances) allows the sacrificial agent to preferentially react with valence band holes, rapidly consuming the holes, preventing the recombination of photogenerated electrons and holes, and improving the utilization rate of photogenerated electrons; unrecombined photogenerated electrons can further participate in H... + The reduction reaction significantly improves the consumption efficiency of free hydrogen ions in the system, while the oxidation products of the sacrificial agent do not cause secondary pollution to the electrolytic phosphating system and do not affect the phosphating film formation process. Simultaneously, the solution pH value is changed by altering the H+... + Concentration and the surface charge state of the catalyst significantly affect the hole trapping tendency. Acidic conditions are more conducive to H2 evolution, which is compatible with the acidic environment of the electrolytic phosphating bath, allowing for full utilization of photocatalytic hydrogen removal. Furthermore, the acidic environment of the electrolytic phosphating bath matches the optimal pH range for photocatalytic hydrogen removal, enabling the photocatalytic effect to sustainably and precisely consume excess free H2 in the bath. + By controlling the ratio of total acidity to free acidity within the process threshold, the stability of the phosphating bath is maintained, ensuring the film-forming kinetics of the phosphating film and improving the uniformity, density, and protective performance of the film layer.
[0010] The technical solution adopted by this invention to solve its technical problem is: This invention provides a cadmium sulfide nanorod, the raw materials of which include: 3-6 wt% cadmium source, 1.5-4 wt% sulfur source, 0.3-0.5 wt% compound morphology control agent, pH adjuster to adjust pH to 9-9.5, and the balance being water; The composite morphology control agent includes anionic surfactants, dodecylpyrrolidone, and mercaptocarboxylic acids; the anionic surfactants include one or more of sodium dodecylbenzenesulfonate (SDBS), sodium dodecyl sulfate (SDS), and sodium dodecyl sulfonate (SLS), and the mercaptocarboxylic acids include one or two of thioglycolic acid (TGA) and mercaptopropionic acid (MPA). Cadmium sulfide nanorods are prepared via a hydrothermal reaction.
[0011] Furthermore, the mass ratio of the anionic surfactant, dodecylpyrrolidone, and mercaptocarboxylic acid is (1-2):(1-2):1.
[0012] Furthermore, the cadmium source includes one or more of cadmium nitrate, cadmium acetate, cadmium chloride, and cadmium sulfate.
[0013] Furthermore, the sulfur source includes one or more of sodium thiosulfate, thiourea, sodium sulfite, and sodium sulfide.
[0014] Furthermore, the pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, ammonium bicarbonate, and triethanolamine.
[0015] This invention provides a method for preparing the above-mentioned cadmium sulfide nanorods, comprising the following steps: After mixing cadmium source, sulfur source, compound morphology control agent, pH adjuster and water, hydrothermal reaction was carried out, followed by centrifugation, washing and drying to obtain cadmium sulfide nanorods.
[0016] Further, under stirring, the cadmium source, compound morphology control agent, sulfur source and pH adjuster are added to the water in sequence and mixed.
[0017] Preferably, the stirring rate is 300-500 r / min.
[0018] Furthermore, the hydrothermal reaction is carried out at a temperature of 160-180℃ for 6-12 hours.
[0019] Furthermore, the centrifugation speed is 8000-10000 r / min, and the time is 10-15 min.
[0020] Furthermore, the washing process involves water and ethanol.
[0021] Furthermore, the drying is vacuum drying, with a temperature of 60-80℃, a vacuum degree of (-0.08)~(-0.1)MPa, and a time of 12-14h.
[0022] This invention provides a cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect, comprising a substrate and a composite coating. The raw materials of the composite coating include the following components by weight percentage: 8%-15% of the above-mentioned cadmium sulfide nanorods, 70%-75% of the binder, 2%-5% of the dispersant, 1%-3% of the film-forming aid, 0.5%-2% of the coupling agent, and the balance being water.
[0023] Furthermore, the substrate is an inert conductor substrate.
[0024] Furthermore, the adhesive aid includes one or more of waterborne epoxy resin, waterborne polyurethane, and acrylate adhesive.
[0025] Furthermore, the dispersant includes one or more of sodium polycarboxylate, sodium hexametaphosphate, and polyvinylpyrrolidone.
[0026] Furthermore, the film-forming aid includes one or more of propylene glycol methyl ether, ethylene glycol butyl ether, and dodecyl alcohol ester.
[0027] Furthermore, the coupling agent includes one or more of the following: silane coupling agents KH550 and KH560, and titanate coupling agents.
[0028] This invention provides a method for preparing the above-mentioned cadmium sulfide nanorod composite coated electrode based on photocatalytic effect, comprising the following steps: After mixing the adhesive, dispersant, coupling agent, cadmium sulfide nanorods, film-forming aid and water, a composite coating liquid is obtained. The substrate is first immersed in the composite coating liquid, then removed, dried, sandblasted and cured. Then it is immersed in the composite coating liquid a second time, then removed, dried, sandblasted and cured to obtain a cadmium sulfide nanorod composite coating electrode plate based on photocatalytic effect. Further, under stirring conditions, the thickener, dispersant, coupling agent, cadmium sulfide nanorods, and film-forming aid are added to the water in sequence and mixed.
[0029] Furthermore, the substrate is an inert conductor substrate.
[0030] Furthermore, the substrate is a titanium mesh.
[0031] Furthermore, the substrate undergoes degreasing and derusting treatment.
[0032] Preferably, the degreasing and rust removal is performed by heating the substrate in a water bath with hydrochloric acid.
[0033] More preferably, the concentration of hydrochloric acid is 10%~15%, the water bath heating temperature is 80~90℃, and the time is 30~40min.
[0034] Furthermore, during the first immersion in the composite coating liquid, including removal, drying, sandblasting, and curing, the substrate is vertically immersed in the composite coating liquid and pulled up at a constant speed of 2-3 cm / min; drying is carried out at room temperature with ventilation for 10-15 minutes; sandblasting uses 120-180 mesh fine white corundum abrasive as the sandblasting medium, with the sandblasting pressure adjusted to 0.15-0.25 MPa, and the sandblasting gun is at a 30°-45° angle to the coating surface, with reciprocating sandblasting for 2-3 minutes; the curing temperature is 120-150℃, and the time is 2-4 hours.
[0035] Furthermore, during the second impregnation of the composite coating liquid, including removal, drying, sandblasting, and curing, the substrate is vertically immersed in the composite coating liquid and pulled up at a constant speed of 2-3 cm / min; drying is carried out at room temperature with ventilation for 10-15 minutes; sandblasting uses 120-180 mesh fine white corundum abrasive as the sandblasting medium, with the sandblasting pressure adjusted to 0.1-0.15 MPa, and the sandblasting gun is at a 30°-45° angle to the coating surface, with reciprocating sandblasting for 1-2 minutes; the curing temperature is 120-150℃, and the time is 2-4 hours.
[0036] This invention provides an electrolytic phosphating process based on photocatalytic effect to regulate free acid, comprising the following steps: Electrolytic phosphating is performed using an inert electrode plate as the anode, the workpiece to be phosphated as the cathode, and an electrolytic phosphating solution containing a sacrificial agent as the electrolyte. During the electrolytic phosphating process, the aforementioned cadmium sulfide nanorod composite coated electrode plate based on the photocatalytic effect is placed in the electrolytic phosphating solution containing a sacrificial agent and irradiated with ultraviolet light. The effective area and ultraviolet light intensity of the composite coated electrode plate are adjusted according to the generation of free acid during the electrolytic phosphating process.
[0037] Furthermore, the wavelength of the ultraviolet light is 320-400nm.
[0038] Furthermore, the sacrificial agent is a reducing substance, such as one or more of alcohols, organic acids, and thiosulfates.
[0039] Preferably, the sacrificial agent is one or more of triethanolamine, citric acid, sodium thiosulfate, and potassium thiosulfate.
[0040] Furthermore, the electrolytic phosphating solution containing sacrificial agent comprises: 60-80 g / L zinc dihydrogen phosphate, 20-40 g / L zinc nitrate, 15-30 mL / L 85% phosphoric acid, 3-5 g / L sacrificial agent, and the balance being water.
[0041] Furthermore, the stirring rate of the electrolytic phosphating is 100~200 r / min, and the temperature is 35~40℃.
[0042] Furthermore, a sacrificial agent is added at intervals during the electrolytic phosphating process.
[0043] The beneficial effects of this invention are: The cadmium sulfide nanorods prepared by this invention based on a compound morphology control agent have high phase purity and good crystallinity, and have a nanorod structure and good dispersibility, which is conducive to exposing more active sites and improving photocatalytic performance. The cadmium sulfide nanorod composite coating electrode structure of the present invention is stable and can be used to control (reduce) free acid in the electrolytic phosphating process. The resulting phosphating film is dense and continuous with no pinholes or cracks, and has better performance. Attached Figure Description
[0044] Figure 1 Electron micrographs of cadmium sulfide prepared in Example 3 and Comparative Examples 1-4 of this invention; Figure 2 The X-ray diffraction patterns of cadmium sulfide prepared in Example 3 and Comparative Example 1 of this invention are shown below. Figure 3 Metallographic images of the phosphating films prepared in Example 3 and Comparative Examples 1-8 of this invention. Detailed Implementation
[0045] The present invention will be further described below with reference to embodiments.
[0046] The following will clearly and completely describe the concept, specific solutions, and technical effects of the present invention with reference to embodiments, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. The various technical features in the present invention can be combined interactively without contradicting each other.
[0047] This invention provides cadmium sulfide nanorods, the raw materials of which comprise the following components by weight percentage: 3%-6% industrial-grade cadmium source (purity ≥98.0%), 1.5%-4% industrial-grade sulfur source (purity ≥98.0%), 0.3%-0.5% industrial-grade compound morphology control agent (purity ≥99.0%), pH adjuster to adjust pH to 9-9.5, and the balance being industrial-grade deionized water. Cadmium sulfide nanorods are prepared via a hydrothermal reaction.
[0048] Furthermore, the cadmium source includes one or more of industrial-grade cadmium nitrate, cadmium acetate, cadmium chloride, and cadmium sulfate.
[0049] Furthermore, the sulfur source includes one or more of industrial-grade sodium thiosulfate, thiourea (CH4N2S), sodium sulfite, and sodium sulfide.
[0050] Furthermore, the compound morphology control agent includes an industrial-grade anionic surfactant, dodecylpyrrolidone, and a mercaptocarboxylic acid; the anionic surfactant includes one or more of sodium dodecylbenzenesulfonate (SDBS), sodium dodecyl sulfate (SDS), and sodium dodecyl sulfonate (SLS), and the mercaptocarboxylic acid includes one or two of thioglycolic acid (TGA) and mercaptopropionic acid (MPA).
[0051] Preferably, the compound morphology control agent is sodium dodecylbenzenesulfonate (SDBS), dodecylpyrrolidone (DPL), and thioglycolic acid (TGA) in a mass ratio of 1:2:1, which can be adjusted to 2:1:1 or 1:1:1 as needed.
[0052] Furthermore, the pH adjuster includes one or more of industrial-grade sodium hydroxide, potassium hydroxide, ammonium bicarbonate, and triethanolamine.
[0053] This invention provides a method for preparing cadmium sulfide nanorods, comprising the following steps: S101. Use industrial-grade deionized water as a solvent in a reaction vessel, turn on magnetic stirring at room temperature, and control the stirring rate at 300-500 r / min. S102. Slowly add 3%-6% industrial-grade cadmium source (based on the total mass of the preset reaction solution) to the solvent, and stir continuously for 20-30 minutes until the cadmium source is completely dissolved; S103. Keeping the stirring constant, add 0.3%-0.5% (based on the total mass of the preset reaction solution) of industrial-grade compound morphology control agent to the solution obtained in step S102, and continue stirring for 15-20 minutes until the compound morphology control agent is completely dissolved; S104. Keeping the stirring constant, add 1.5%-4% industrial-grade sulfur source (based on the total mass of the preset reaction solution) to the mixed solution obtained in step S103, and stir for 10-15 minutes until completely dissolved; S105. Keep stirring constant and slowly add pH adjuster at a rate of 1-2 drops / second, while monitoring the pH value of the solution in real time with a pH meter until the solution pH stabilizes at 9.0-9.5; S106. Add industrial-grade deionized water to the preset total mass of the reaction solution, and continue stirring for 5-10 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. Seal the polytetrafluoroethylene-lined container containing the hydrothermal reaction solution into the hydrothermal reactor, tighten the lid, place it in a forced-air drying oven, raise the temperature to 160-180℃ at a rate of 3-5℃ / min, and maintain the temperature for 6-12 hours. After the reaction is complete, turn off the forced-air drying oven and allow the reactor to cool naturally to room temperature (20-25℃). After cooling, remove the reaction solution. S108. Transfer the reaction solution after hydrothermal reaction to a centrifuge and centrifuge at 8000-10000 r / min for 10-15 min, and collect the bottom precipitate; wash the precipitate with industrial grade deionized water 3-4 times, centrifuging for 5-10 min after each wash; then wash the precipitate with industrial grade anhydrous ethanol 1-2 times, centrifuging for 5-10 min after each wash; S109. Place the washed precipitate in a vacuum drying oven at 60-80℃, with the vacuum degree controlled at (-0.08)~(-0.1)MPa, and dry for 12-14h. After drying, allow it to cool naturally to room temperature to obtain pure, low-cost industrial cadmium sulfide nanorods.
[0054] This invention provides a cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect, comprising a substrate and a composite coating. The raw materials of the composite coating include the following components by weight percentage: 8%-15% cadmium sulfide nanorods, 70%-75% industrial-grade binder, 2%-5% industrial-grade dispersant, 1%-3% industrial-grade film-forming aid, 0.5%-2% industrial-grade coupling agent, and the balance being industrial-grade deionized water. It is used in electrolytic phosphating processes.
[0055] Furthermore, the substrate is an inert conductor substrate with an area of 580-620 cm². 2 The inertness of the substrate helps maintain its stability; during the photocatalytic reaction, a small amount of charge may accumulate on the coating surface, but the conductivity of the substrate can quickly dissipate the accumulated charge, maintain the charge balance on the coating surface, avoid charge accumulation inhibiting subsequent photoexcitation, and ensure the continuous and stable progress of the photocatalytic reaction.
[0056] Preferably, the substrate is a titanium mesh.
[0057] Furthermore, the adhesive aid includes one or more of industrial-grade waterborne epoxy resin, waterborne polyurethane, and acrylate adhesive.
[0058] Furthermore, the dispersant includes one or more of industrial-grade sodium polycarboxylate, sodium hexametaphosphate, and polyvinylpyrrolidone.
[0059] Furthermore, the film-forming aid includes one or more of industrial-grade propylene glycol methyl ether, ethylene glycol butyl ether, and dodecyl alcohol ester.
[0060] Furthermore, the coupling agent includes one or more of the following: industrial-grade silane coupling agents KH550 and KH560, and titanate coupling agents.
[0061] This invention provides a method for preparing a cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect, comprising the following steps: S201. Place industrial-grade deionized water as solvent in a reaction vessel, start stirring at a rate of 400~600 r / min at room temperature, slowly add 70%-75% industrial-grade adhesion promoter (based on the total mass of the preset composite coating liquid), and continue stirring for 30~40 min until completely dissolved; S202. Keep stirring, add 2%-5% industrial-grade dispersant (based on the total mass of the pre-set composite coating liquid) to the solution obtained in S201, and continue stirring for 20-25 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 0.5%-2% industrial-grade coupling agent (based on the total mass of the preset composite coating liquid) to the mixed solution obtained in S202, and stir for 15-20 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 8%-15% of pre-made cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) to the solution obtained in S203 in 3-5 batches, with an interval of 5-10 minutes between each batch. After the addition is complete, continue stirring for 40-60 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 200~300r / min, add 1%-3% industrial-grade film-forming aid (based on the total mass of the preset composite coating liquid) to the composite adhesive obtained in S204, and stir for 10~15min until the mixture is uniform; S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, and continue stirring at a stirring rate of 200~300r / min for 5-10min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid. Seal and let stand for later use. S207. Place the substrate in 10%~15% industrial grade dilute hydrochloric acid and heat in a water bath at 80~90℃ for 30~40 minutes to remove oil and rust. After removing it, rinse it with industrial grade deionized water until neutral and drain the surface moisture. S208. Place the substrate treated with S207 in a 60~70℃ forced-air drying oven and dry for 2~3 hours. Cool to room temperature before use. S209. Immerse the substrate pretreated in S208 vertically into the composite coating liquid obtained in S206, and pull it up at a constant speed of 2~3cm / min. After pulling up, place it in a ventilated place at room temperature for pre-drying for 10~15min to form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in a sandblasting device, use 120~180 mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.15~0.25MPa, and keep the sandblasting gun at a 30°~45° angle to the coating surface. Sandblast for 2~3 minutes in a slow, uniform reciprocating motion. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it dry with nitrogen. S211. Place the activated electrode plate after sandblasting with S210 in a forced-air drying oven and heat it to 120~150℃ at a heating rate of 2~4℃ / min. Then, keep it at the temperature for 2~4 hours and let it cool naturally to room temperature (20~25℃) after curing. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.1~0.15MPa and the sandblasting time being 1~2min; The primary function of the first coating layer is to achieve a strong bond with the titanium mesh substrate, sealing pores and defects on the titanium mesh surface to prevent subsequent coatings from peeling off directly. Simultaneously, it constructs a conductive-photocatalytic transition layer to prevent insufficient adhesion between the substrate and the coating interface. The second coating layer compensates for pinholes, cracks, and thin areas in the first layer, improving overall coating uniformity. It also adds cadmium sulfide active components to ensure the number of photocatalytic active sites.
[0062] The first sandblasting process enhances the adhesion between the first and second coating layers by disrupting the smooth, dense surface of the first semi-cured coating. This creates microscopic roughness and pits, allowing the second coating liquid to fully penetrate and embed, preventing delamination, peeling, and detachment of the two coating layers. The second sandblasting process breaks down the coating layer, exposing the cadmium sulfide nanorods. The aqueous epoxy resin encapsulates the CdS nanorods, and sandblasting physically removes the surface epoxy coating, releasing photocatalytic active sites and preventing the active components from being completely encapsulated by the resin and losing their catalytic activity. This micro-roughened structure enhances light-harvesting capabilities, and the rough surface increases light scattering / absorption, thereby improving photocatalytic efficiency.
[0063] The first sandblasting (high pressure + long time) results in greater intensity. The first semi-cured coating is thicker and has a softer structure, requiring sufficient sandblasting force and time to form effective micro-anchors. It also deeply breaks down the surface resin coating, laying the foundation for secondary bonding and active exposure. Insufficient pressure or time leads to insufficient roughness and poor interlayer bonding. The second sandblasting (low pressure + short time) has relatively lower intensity. The second coating is thinner, and the electrode has already undergone one curing and sandblasting cycle, providing sufficient substrate roughness. Excessive intensity will over-abrade the coating, causing it to thin, peel off, or even expose the titanium mesh substrate, negating the composite coating's function. Low pressure and short time only lightly polish the surface, just enough to expose the CdS active sites while preserving the complete coating, balancing mechanical strength, bonding strength, and photocatalytic activity.
[0064] S213. Perform visual inspection on the cooled electrode plate, requiring the coating surface to be uniform, without cracks, bubbles, or peeling, and with a uniform distribution of micro-rough structure; after passing the inspection, seal and store it to obtain the cadmium sulfide nanorod composite coated electrode plate based on the photocatalytic effect.
[0065] This invention provides an electrolytic phosphating process based on photocatalytic effect to regulate free acid. It utilizes an electrostatically photocatalytic composite coated electrode to regulate free acid. The aforementioned cadmium sulfide nanorod composite coated electrode is used in conjunction with a conventional electrolytic phosphating inert electrode. The composite coated electrode requires no electricity; it is simply immersed in the phosphating bath and generates a photocatalytic effect through light irradiation. Citric acid and other photocatalytic sacrificial agents are used to precisely consume excess free H₂ in the bath. + It maintains a stable acid ratio in the bath solution and, in conjunction with the electrochemical reaction of conventional inert plates, achieves high-quality, slag-free electrolytic phosphating treatment of metal wires, significantly improving the uniformity, density, and adhesion performance of the phosphating film.
[0066] The electrolytic phosphating process includes the following steps: S301. Electrode Arrangement and Light Source Installation: Install conventional electrolytic phosphating inert electrodes (titanium plate substrate with ruthenium-iridium coating, total effective area 1~1.5m²) in the electrolytic phosphating tank as the main anode, connected to the positive terminal of the electrolysis power supply; immerse cadmium sulfide nanorod composite coated electrodes (4-6 pieces, total effective area 0.20-0.40m²) in the circulating phosphating solution below the phosphating tank, ensuring that they do not contact the conventional inert electrodes or the cathode substrate; arrange a dedicated photocatalytic light source at the bottom of the tank corresponding to the position of the composite coated electrodes, and adjust the angle of the light source to ensure that the light fully covers the surface of the composite coated electrodes; S302. Solution Preparation and Photocatalytic Preheating: The special electrolytic phosphating solution formula used in the electrolytic phosphating process includes, per 1L of electrolytic phosphating solution: 60-80g of industrial-grade zinc dihydrogen phosphate, 20-40g of industrial-grade zinc nitrate, 15-30mL of industrial-grade 85% phosphoric acid, and 3-5g of industrial-grade citric acid, plus industrial-grade deionized water to 1L; when preparing the solution, dissolve the above components in sequence at room temperature, stirring at a rate of 150-200r / min, and let stand for 5-10min after all components are completely dissolved. The initial total acidity to free acidity ratio of the solution should be controlled at 15~20:1. Prepare an electrolytic phosphating solution of 200-300L according to the above formula, inject it into the electrolytic phosphating tank, heat it to 35-40℃, and maintain the stirring speed at 100-200r / min; turn on the photocatalytic light source and preheat it for 10-20min. The light transmission process is continuous and uninterrupted from the preheating to the end of the process. S303. Substrate pretreatment and production line connection: The raw material coiled steel wire (diameter 3~6mm, single coil weight 300~500kg) is sequentially connected to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted winding machine. S304. Set the electrolysis process parameters. The current density of the conventional inert energized anode is 5~25A / dm², the wire speed is 0.6~1.6m / s, turn on the electrolytic phosphating power supply and the inverted winding machine, and carry out continuous electrolytic phosphating treatment on the wire. At the same time, every 10~12 hours of continuous production, add 0.1~0.2g / L of industrial-grade citric acid to the bath to maintain the effective concentration of the sacrificial agent. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire. After phosphate treatment, the wire is rinsed in a post-washing tank to remove residual bath solution on the surface. After natural air drying or low-temperature drying, the wire is collected to obtain a phosphated wire with a uniform and dense surface and no pinhole cracks.
[0067] Furthermore, the photocatalytic light source mentioned in step S301 is a 320-400nm ultraviolet light source, the distance between the light source and the composite coated electrode is 40-55cm, and the light intensity is controlled at 8-10mW / cm².
[0068] Furthermore, the stirring rate in step S302 is 100~200 r / min, and the bath temperature is 35~40℃.
[0069] Furthermore, the photocatalytic effect described in step S304 occurs simultaneously with the electrolytic phosphating process. The composite coated electrode is not energized throughout the entire process; the excess free H₂ generated by the electrochemical reaction in the bath solution is consumed solely through the photocatalytic reaction. + No manual adjustment of the free acid in the bath solution is required.
[0070] The electrolytic phosphating process of this invention employs a dual "anodine" system combining a passive photocatalytic composite coated electrode plate without electricity and a conventional inert electrode plate with electricity. This achieves functional separation of "electrochemical reaction for film formation and photocatalytic reaction for acid adjustment," ensuring no interference between the two processes. The phosphating solution is free of sodium fluoride, using citric acid as the sole photocatalytic sacrificial agent, resulting in no secondary pollution and significantly improving the photocatalytic acid reduction efficiency. The composite coated electrode plates are arranged in a small-size, small-area dispersed manner, enabling uniform acid reduction throughout the bath and avoiding film defects caused by excessively high levels of free acid in certain areas. The entire process requires no manual adjustment of the bath acid ratio, achieving slag-free production, reducing process maintenance costs, and producing a uniform and dense phosphating film with significantly improved adhesion and protective performance.
[0071] Example 1 A method for preparing cadmium sulfide nanorods includes the following steps: The raw materials, by weight percentage, include: 3% industrial-grade cadmium chloride, 1.5% industrial-grade thiourea, 0.3% compound morphology control agent (SDBS: dodecylpyrrolidone: TGA = 1:1:1, w / w / w), industrial-grade sodium hydroxide to adjust the pH to 9, and the remainder is industrial-grade deionized water.
[0072] S101. Use industrial-grade deionized water as a solvent and place it in a reaction vessel. Turn on the magnetic stirrer at a rate of 300 r / min at room temperature. S102. Add 3% cadmium chloride (based on the total mass of the pre-set reaction solution) to the solvent and stir continuously for 20 minutes until completely dissolved; S103. Keep stirring, add 0.3% of the compound morphology control agent (based on the total mass of the preset reaction solution), and continue stirring for 15 minutes until completely dissolved; S104. While keeping the stirring constant, add 1.5% thiourea (based on the total mass of the preset reaction solution) to the mixed solution and stir for 10 minutes until completely dissolved; S105. While maintaining constant stirring, add industrial-grade sodium hydroxide solution (50% mass concentration) at a rate of 1 drop / second, and monitor the pH value in real time until it stabilizes at 9.0; S106. Add water to the preset total mass of the reaction solution with industrial-grade deionized water, and continue stirring for 5 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. The hydrothermal reaction solution is loaded into a polytetrafluoroethylene liner and sealed into a hydrothermal reactor. The temperature is increased to 160°C at a rate of 3°C / min, and the reaction is kept at a constant temperature for 6 hours. After the reaction is completed, the mixture is naturally cooled to room temperature. S108. Transfer the reaction solution to a centrifuge and centrifuge at 8000 r / min for 10 min. Collect the bottom precipitate and wash it 3 times with industrial-grade deionized water and 1 time with industrial-grade anhydrous ethanol. Centrifuge for 5 min after each wash. S109. The washed precipitate was placed in a vacuum drying oven at 60℃ (vacuum degree -0.08MPa) and dried for 12h, and then allowed to cool naturally to room temperature to obtain cadmium sulfide nanorods.
[0073] A method for preparing a cadmium sulfide nanorod composite coated electrode based on photocatalytic effect includes the following steps: The raw materials, by weight percentage, include: 8% cadmium sulfide nanorods, 70% industrial-grade waterborne epoxy resin, 2% industrial-grade sodium polycarboxylate, 1% industrial-grade propylene glycol methyl ether, 0.5% industrial-grade silane coupling agent KH550, and the balance being industrial-grade deionized water; mixed with 580cm 2 Titanium mesh inert conductor substrate.
[0074] S201. Use industrial-grade deionized water as a solvent in a reaction vessel, start stirring at 400 r / min at room temperature, add 70% waterborne epoxy resin (based on the total mass of the preset composite coating liquid), and continue stirring for 30 min until completely dissolved. S202. While keeping the stirring constant, add 2% sodium polycarboxylate (based on the total mass of the preset composite coating liquid) and continue stirring for 20 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 0.5% KH550 (based on the total mass of the preset composite coating liquid) to the mixed solution, and stir for 15 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 8% cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) in 3 batches, with an interval of 5 minutes between each batch. After the addition is complete, continue stirring for 40 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 200 r / min, add 1% propylene glycol methyl ether (based on the total mass of the preset composite coating liquid), and stir for 10 min until the mixture is uniform. S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, continue stirring at 200 r / min for 5 min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid, seal and let stand for later use. S207. Select titanium mesh as the inert conductor substrate, place it in 10% industrial grade dilute hydrochloric acid, heat it in an 80℃ water bath for 30 minutes to remove oil and rust, take it out and rinse it with industrial grade deionized water until neutral, and drain the surface moisture. S208. Place the treated titanium mesh in a 60℃ forced-air drying oven for 2 hours, and cool it to room temperature before use. S209. Immerse the pretreated substrate vertically into the composite coating liquid and pull it up at a constant speed of 2 cm / min. After pulling up, place it in a ventilated place at room temperature for 10 min to pre-dry and form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in the sandblasting equipment, use 120-mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.15MPa, and make a 30° angle between the sandblasting gun and the coating surface. Slowly and uniformly reciprocate for 2 minutes. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it with nitrogen to drain the water. S211. Place the sandblasted activated electrode plate in a forced-air drying oven, raise the temperature to 120°C at a rate of 2°C / min, and cure at a constant temperature for 2 hours. After curing, allow it to cool naturally to room temperature. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.1MPa and the sandblasting time being 1min; S213. After cooling, the electrode plate is visually inspected. The coating surface is uniform, without cracks, bubbles, or peeling, and the micro-rough structure is evenly distributed. After passing the inspection, the plate is sealed and stored to obtain the composite coated electrode plate.
[0075] An electrolytic phosphating process based on photocatalytic effect to regulate free acid includes the following steps: S301. Electrode arrangement and light source installation: Conventional electrolytic phosphating inert electrodes (titanium substrate with ruthenium-iridium coating, total effective area 1m²) are used. 2 The electrode is installed inside the electrolytic phosphating cell as the main anode and connected to the positive terminal of the electrolytic power supply; four composite coated electrode plates (each with an area of 580 cm²) are installed. 2 The total effective area is 0.232m². 2 The electrode is immersed in the circulating phosphating solution below the phosphating tank, ensuring that it does not come into contact with the conventional inert electrode plate or cathode substrate. A 320nm ultraviolet light source is placed at the bottom of the tank corresponding to the position of the composite coating electrode plate, with a distance of 40cm between the light source and the composite coating electrode plate and a light intensity of 8mW / cm². 2 Adjust the angle of the light source to ensure that the light fully covers the surface of the coated electrode plate; S302. Preparation of Electrolytic Phosphating Solution and Photocatalytic Preheating: Prepare 200L of electrolytic phosphating solution according to the formula of 60g of industrial-grade zinc dihydrogen phosphate, 20g of industrial-grade zinc nitrate, 15mL of industrial-grade 85% phosphoric acid, 2g of industrial-grade citric acid, and the balance being industrial-grade deionized water per 1L of electrolytic phosphating solution and pour it into the electrolytic phosphating tank. Heat to 35℃ and maintain a stirring speed of 100r / min. Turn on the ultraviolet light source and preheat for 10min. The light transmission process is continuous and uninterrupted from the start of preheating to the end of the process. S303. Substrate pretreatment and production line connection: Connect the 3mm raw material coiled steel wire sequentially to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted take-up machine; S304. Set electrolysis process parameters: The current density of the conventional inert anode is 5 A / dm³. 2 The wire feed speed is 0.6m / s. The electrolytic phosphating power supply and the inverted winding machine are turned on to carry out continuous electrolytic phosphating treatment on the wire. For every 10 hours of continuous production, 0.1g / L of industrial-grade citric acid is added to the bath solution. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire; after phosphate treatment, the wire is rinsed in a post-washing tank to remove residual solution from the surface, and then air-dried to obtain phosphated wire.
[0076] Example 2 A method for preparing cadmium sulfide nanorods includes the following steps: The raw materials, by weight percentage, include: 4.5% industrial-grade cadmium chloride, 2.75% industrial-grade thiourea, 0.4% compound morphology control agent (SDBS: dodecylpyrrolidone: TGA=1:1:1, w / w / w), industrial-grade sodium hydroxide to adjust the pH to 9, and the remainder is industrial-grade deionized water.
[0077] S101. Use industrial-grade deionized water as a solvent in a reaction vessel and start magnetic stirring at 300 r / min at room temperature; S102. Add 4.5% cadmium chloride (based on the total mass of the pre-set reaction solution) to the solvent and stir continuously for 20 minutes until completely dissolved; S103. Keep stirring, add 0.4% of the compound morphology control agent (based on the total mass of the preset reaction solution), and continue stirring for 15 minutes until completely dissolved; S104. While keeping the stirring constant, add 2.75% thiourea (based on the total mass of the preset reaction solution) to the mixed solution and stir for 10 minutes until completely dissolved; S105. While maintaining constant stirring, add industrial-grade sodium hydroxide solution (50% mass concentration) at a rate of 1 drop / second, and monitor the pH value in real time until it stabilizes at 9.0; S106. Add water to the preset total mass of the reaction solution with industrial-grade deionized water, and continue stirring for 5 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. The hydrothermal reaction solution is loaded into a polytetrafluoroethylene liner and sealed into a hydrothermal reactor. The temperature is increased to 170°C at a rate of 4°C / min, and the reaction is kept at a constant temperature for 9 hours. After the reaction is completed, the mixture is allowed to cool naturally to room temperature. S108. Transfer the reaction solution to a centrifuge and centrifuge at 9000 r / min for 12 min. Collect the bottom precipitate and wash it 3 times with industrial-grade deionized water and 1 time with industrial-grade anhydrous ethanol. Centrifuge for 5 min after each wash. S109. The washed precipitate was placed in a vacuum drying oven at 70℃ (vacuum degree -0.09MPa) and dried for 13h, then allowed to cool naturally to room temperature to obtain cadmium sulfide nanorods.
[0078] A method for preparing a cadmium sulfide nanorod composite coated electrode based on photocatalytic effect includes the following steps: The raw materials, by weight percentage, include: 11.5% cadmium sulfide nanorods, 72.5% industrial-grade waterborne epoxy resin, 3.5% industrial-grade sodium polycarboxylate, 2% industrial-grade propylene glycol methyl ether, 1.25% industrial-grade silane coupling agent KH550, with the balance being industrial-grade deionized water; combined with a 600cm² titanium mesh inert conductor substrate.
[0079] S201. Use industrial-grade deionized water as a solvent in a reaction vessel, start stirring at 500 r / min at room temperature, add 72.5% waterborne epoxy resin (based on the total mass of the preset composite coating liquid), and continue stirring for 35 min until completely dissolved; S202. While keeping the stirring constant, add 3.5% sodium polycarboxylate (based on the total mass of the preset composite coating liquid), and continue stirring for 22 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 1.25% KH550 (based on the total mass of the preset composite coating liquid) to the mixed solution, and stir for 17 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 11.5% cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) in 3 batches, with an interval of 5 minutes between each batch. After the addition is complete, continue stirring for 50 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 250 r / min, add 2% propylene glycol methyl ether (based on the total mass of the preset composite coating liquid), and stir for 12 min until uniformly mixed; S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, continue stirring at 250 r / min for 5 min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid, seal and let stand for later use. S207. Select titanium mesh as the inert conductor substrate, place it in 12% industrial grade dilute hydrochloric acid, heat it in an 85℃ water bath for 35 minutes to remove oil and rust, take it out and rinse it with industrial grade deionized water until neutral, and drain the surface moisture. S208. Place the treated titanium mesh in a 65℃ forced-air drying oven for 2.5 hours, and cool it to room temperature before use; S209. Immerse the pretreated substrate vertically into the composite coating liquid and pull it up at a constant speed of 2.5 cm / min. After pulling up, place it in a ventilated place at room temperature for 12 min to pre-dry and form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in a sandblasting device, use 150-mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.2MPa, and hold the sandblasting gun at a 37.5° angle to the coating surface. Slowly and uniformly reciprocate for 2.5 minutes. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it dry with nitrogen. S211. Place the sandblasted activated electrode plate in a forced-air drying oven, raise the temperature to 135℃ at a rate of 3℃ / min, and cure at a constant temperature for 3 hours. After curing, allow it to cool naturally to room temperature. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.125MPa and the sandblasting time being 1.5min; S213. After cooling, the electrode plate is visually inspected. The coating surface is uniform, without cracks, bubbles, or peeling, and the micro-rough structure is evenly distributed. After passing the inspection, the plate is sealed and stored to obtain the composite coated electrode plate.
[0080] An electrolytic phosphating process based on photocatalytic effect to regulate free acid includes the following steps: S301. Electrode Arrangement and Light Source Installation: A conventional electrolytic phosphating inert electrode (titanium plate substrate with ruthenium-iridium coating, total effective area 1.25m²) is installed in the electrolytic phosphating tank as the main anode and connected to the positive terminal of the electrolytic power supply; four composite coated electrodes (each with an area of 600cm², total effective area 0.24m²) are immersed in the circulating phosphating solution below the phosphating tank, ensuring that they do not contact the conventional inert electrode or the cathode substrate. A 365nm ultraviolet light source is arranged at the bottom of the tank corresponding to the position of the composite coated electrode, with a distance of 48cm between the light source and the composite coated electrode and a light intensity of 9mW / cm². The angle of the light source is adjusted to ensure that the light fully covers the surface of the coated electrode. S302. Preparation of Electrolytic Phosphating Solution and Photocatalytic Preheating: Prepare 250L of electrolytic phosphating solution according to the following formula: 1L of electrolytic phosphating solution contains 60g of industrial-grade zinc dihydrogen phosphate, 20g of industrial-grade zinc nitrate, 15mL of industrial-grade 85% phosphoric acid, 2g of industrial-grade citric acid, and the balance is industrial-grade deionized water. Pour the solution into the electrolytic phosphating tank, heat to 38℃, and maintain a stirring speed of 150r / min. Turn on the ultraviolet light source and preheat for 10min. The light transmission process is continuous and uninterrupted from the start of preheating to the end of the process. S303. Substrate pretreatment and production line connection: Connect the 4.5mm raw material coiled steel wire sequentially to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted winding machine; S304. Set the electrolysis process parameters: The current density of the conventional inert energized anode is 15A / dm², the wire speed is 1.1m / s, turn on the electrolytic phosphating power supply and the inverted take-up machine, and carry out continuous electrolytic phosphating treatment on the wire. For every 10 hours of continuous production, add 0.15g / L of industrial-grade citric acid to the bath solution. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire; after phosphate treatment, the wire is rinsed in a post-washing tank to remove residual solution from the surface, and then air-dried to obtain phosphated wire.
[0081] Example 3 A method for preparing cadmium sulfide nanorods includes the following steps: The raw materials, by weight percentage, include: 6% industrial-grade cadmium chloride, 4% industrial-grade thiourea, 0.5% compound morphology control agent (SDBS: dodecylpyrrolidone: TGA=1:2:1, w / w / w), industrial-grade sodium hydroxide to adjust the pH to 9.5, and the remainder is industrial-grade deionized water.
[0082] S101. Use industrial-grade deionized water as a solvent in a reaction vessel and start magnetic stirring at 300 r / min at room temperature; S102. Add 6% cadmium chloride (based on the total mass of the pre-set reaction solution) to the solvent and stir continuously for 30 minutes until completely dissolved; S103. Keep stirring, add 0.5% of the compound morphology control agent (based on the total mass of the preset reaction solution), and continue stirring for 20 minutes until completely dissolved; S104. While keeping the stirring constant, add 4% thiourea (based on the total mass of the preset reaction solution) to the mixed solution and stir for 15 minutes until completely dissolved; S105. While maintaining constant stirring, add industrial-grade sodium hydroxide solution (50% mass concentration) at a rate of 1 drop / second, and monitor the pH value in real time until it stabilizes at 9.5; S106. Add water to the preset total mass of the reaction solution with industrial-grade deionized water, and continue stirring for 5 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. The hydrothermal reaction solution is loaded into a polytetrafluoroethylene liner and sealed into a hydrothermal reactor. The temperature is increased to 180°C at a rate of 5°C / min, and the reaction is kept at a constant temperature for 12 hours. After the reaction is completed, the mixture is allowed to cool naturally to room temperature. S108. Transfer the reaction solution to a centrifuge and centrifuge at 10,000 r / min for 15 min. Collect the bottom precipitate and wash it 4 times with industrial-grade deionized water and 2 times with industrial-grade anhydrous ethanol. Centrifuge for 5 min after each wash. S109. The washed precipitate was placed in a vacuum drying oven at 80℃ (vacuum degree -0.1MPa) and dried for 14h, then allowed to cool naturally to room temperature to obtain cadmium sulfide nanorods.
[0083] A method for preparing a cadmium sulfide nanorod composite coated electrode based on photocatalytic effect includes the following steps: The electrode plate raw materials, by weight percentage, include: 15% cadmium sulfide nanorods, 75% industrial-grade waterborne epoxy resin, 5% industrial-grade sodium polycarboxylate, 3% industrial-grade propylene glycol methyl ether, 2% industrial-grade silane coupling agent KH550, and the balance being industrial-grade deionized water; combined with a 620cm² titanium mesh inert conductor substrate.
[0084] S201. Use industrial-grade deionized water as a solvent in a reaction vessel, start stirring at 600 r / min at room temperature, add 75% water-based epoxy resin (based on the total mass of the preset composite coating liquid), and continue stirring for 40 min until completely dissolved; S202. While keeping the stirring constant, add 5% sodium polycarboxylate (based on the total mass of the preset composite coating liquid) and continue stirring for 25 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 2% KH550 (based on the total mass of the preset composite coating liquid) to the mixed solution, and stir for 20 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 15% cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) in 3 batches, with an interval of 5 minutes between each batch. After the addition is complete, continue stirring for 60 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 300 r / min, add 3% propylene glycol methyl ether (based on the total mass of the preset composite coating liquid), and stir for 15 min until uniformly mixed; S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, and continue stirring at 300 r / min for 5 min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid. Seal and let stand for later use. S207. Select titanium mesh as the inert conductor substrate, place it in 15% industrial grade dilute hydrochloric acid, heat it in a 90℃ water bath for 40 minutes to remove oil and rust, take it out and rinse it with industrial grade deionized water until neutral, and drain the surface moisture. S208. Place the treated titanium mesh in a 70℃ forced-air drying oven for 3 hours, and cool it to room temperature before use; S209. Immerse the pretreated substrate vertically into the composite coating liquid and pull it up at a constant speed of 3 cm / min. After pulling up, place it in a ventilated place at room temperature for 15 min to pre-dry and form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in the sandblasting equipment, use 180-mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.25MPa, and hold the sandblasting gun at a 45° angle to the coating surface. Slowly and uniformly reciprocate for 3 minutes. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it dry with nitrogen. S211. Place the sandblasted activated electrode plate in a forced-air drying oven, raise the temperature to 150°C at a rate of 4°C / min, and cure at a constant temperature for 4 hours. After curing, allow it to cool naturally to room temperature. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.15MPa and the sandblasting time being 2min; S213. After cooling, the electrode plate is visually inspected. The coating surface is uniform, without cracks, bubbles, or peeling, and the micro-rough structure is evenly distributed. After passing the inspection, the plate is sealed and stored to obtain the composite coated electrode plate.
[0085] An electrolytic phosphating process based on photocatalytic effect to regulate free acid includes the following steps: S301. Electrode Arrangement and Light Source Installation: Install conventional electrolytic phosphating inert electrode plates (titanium plate substrate with ruthenium-iridium coating, total effective area 1.5m²) in the electrolytic phosphating tank as the main anode, connected to the positive terminal of the electrolytic power supply; immerse four composite coated electrode plates (single electrode plate area 620cm², total effective area 0.248m²) in the circulating phosphating solution below the phosphating tank, ensuring that they do not contact the conventional inert electrode plates or the cathode substrate; arrange a 400nm ultraviolet light source at the bottom of the tank corresponding to the position of the composite coated electrode plates, with a distance of 55cm between the light source and the composite coated electrode plates and a light intensity of 10mW / cm², adjusting the angle of the light source to ensure that the light fully covers the surface of the coated electrode plates; S302. Preparation of Electrolytic Phosphating Solution and Photocatalytic Preheating: Prepare 300L of electrolytic phosphating solution according to the following formula: 1L of electrolytic phosphating solution contains 60g of industrial-grade zinc dihydrogen phosphate, 20g of industrial-grade zinc nitrate, 15mL of industrial-grade 85% phosphoric acid, 2g of industrial-grade citric acid, and the balance is industrial-grade deionized water. Pour the solution into the electrolytic phosphating tank, heat to 40℃, and maintain a stirring speed of 200r / min. Turn on the ultraviolet light source and preheat for 10min. The light transmission process is continuous and uninterrupted from the start of preheating to the end of the process. S303. Substrate pretreatment and production line connection: Connect the 6mm raw material coiled steel wire sequentially to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted take-up machine; S304. Set the electrolysis process parameters: The current density of the conventional inert energized anode is 25A / dm², the wire speed is 1.6m / s, turn on the electrolytic phosphating power supply and the inverted winding machine, and carry out continuous electrolytic phosphating treatment on the wire. For every 10 hours of continuous production, add 0.2g / L of industrial-grade citric acid to the bath solution. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire; after phosphate treatment, the wire is rinsed in a post-washing tank to remove residual solution from the surface, and then air-dried to obtain phosphated wire.
[0086] Example 4 A method for preparing cadmium sulfide nanorods includes the following steps: The raw materials, by weight percentage, include: 6% industrial-grade cadmium chloride, 4% industrial-grade thiourea, 0.5% compound morphology control agent (SDBS: dodecylpyrrolidone: TGA=2:1:1, w / w / w), industrial-grade sodium hydroxide to adjust the pH to 9.5, and the remainder is industrial-grade deionized water.
[0087] S101. Use industrial-grade deionized water as a solvent in a reaction vessel and start magnetic stirring at 300 r / min at room temperature; S102. Add 6% cadmium chloride (based on the total mass of the pre-set reaction solution) to the solvent and stir continuously for 30 minutes until completely dissolved; S103. Keep stirring, add 0.5% of the compound morphology control agent (based on the total mass of the preset reaction solution), and continue stirring for 20 minutes until completely dissolved; S104. While keeping the stirring constant, add 4% thiourea (based on the total mass of the preset reaction solution) to the mixed solution and stir for 15 minutes until completely dissolved; S105. While maintaining constant stirring, add industrial-grade sodium hydroxide solution (50% mass concentration) at a rate of 1 drop / second, and monitor the pH value in real time until it stabilizes at 9.5; S106. Add water to the preset total mass of the reaction solution with industrial-grade deionized water, and continue stirring for 5 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. The hydrothermal reaction solution is loaded into a polytetrafluoroethylene liner and sealed into a hydrothermal reactor. The temperature is increased to 180°C at a rate of 5°C / min, and the reaction is kept at a constant temperature for 12 hours. After the reaction is completed, the mixture is allowed to cool naturally to room temperature. S108. Transfer the reaction solution to a centrifuge and centrifuge at 10,000 r / min for 15 min. Collect the bottom precipitate and wash it 4 times with industrial-grade deionized water and 2 times with industrial-grade anhydrous ethanol. Centrifuge for 5 min after each wash. S109. The washed precipitate was placed in a vacuum drying oven at 80℃ (vacuum degree -0.1MPa) and dried for 14h, then allowed to cool naturally to room temperature to obtain cadmium sulfide nanorods.
[0088] A method for preparing a cadmium sulfide nanorod composite coated electrode based on photocatalytic effect includes the following steps: The raw materials, by weight percentage, include: 15% cadmium sulfide nanorods, 75% industrial-grade waterborne epoxy resin, 5% industrial-grade sodium polycarboxylate, 3% industrial-grade propylene glycol methyl ether, 2% industrial-grade silane coupling agent KH550, and the balance being industrial-grade deionized water; mixed with 620cm 2 Titanium mesh inert conductor substrate.
[0089] S201. Use industrial-grade deionized water as a solvent in a reaction vessel, start stirring at 600 r / min at room temperature, add 75% water-based epoxy resin (based on the total mass of the preset composite coating liquid), and continue stirring for 40 min until completely dissolved; S202. While keeping the stirring constant, add 5% sodium polycarboxylate (based on the total mass of the preset composite coating liquid) and continue stirring for 25 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 2% KH550 (based on the total mass of the preset composite coating liquid) to the mixed solution, and stir for 20 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 15% cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) in 3 batches, with an interval of 5 minutes between each batch. After the addition is complete, continue stirring for 60 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 300 r / min, add 3% propylene glycol methyl ether (based on the total mass of the preset composite coating liquid), and stir for 15 min until uniformly mixed; S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, and continue stirring at 300 r / min for 5 min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid. Seal and let stand for later use. S207. Select titanium mesh as the inert conductor substrate, place it in 15% industrial grade dilute hydrochloric acid, heat it in a 90℃ water bath for 40 minutes to remove oil and rust, take it out and rinse it with industrial grade deionized water until neutral, and drain the surface moisture. S208. Place the treated titanium mesh in a 70℃ forced-air drying oven for 3 hours, and cool it to room temperature before use; S209. Immerse the pretreated substrate vertically into the composite coating liquid and pull it up at a constant speed of 3 cm / min. After pulling up, place it in a ventilated place at room temperature for 15 min to pre-dry and form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in the sandblasting equipment, use 180-mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.25MPa, and hold the sandblasting gun at a 45° angle to the coating surface. Slowly and uniformly reciprocate for 3 minutes. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it dry with nitrogen. S211. Place the sandblasted activated electrode plate in a forced-air drying oven, raise the temperature to 150°C at a rate of 4°C / min, and cure at a constant temperature for 4 hours. After curing, allow it to cool naturally to room temperature. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.15MPa and the sandblasting time being 2min; S213. After cooling, the electrode plate is visually inspected. The coating surface is uniform, without cracks, bubbles, or peeling, and the micro-rough structure is evenly distributed. After passing the inspection, the plate is sealed and stored to obtain the composite coated electrode plate.
[0090] An electrolytic phosphating process based on photocatalytic effect to regulate free acid includes the following steps: S301. Electrode Arrangement and Light Source Installation: Install conventional electrolytic phosphating inert electrode plates (titanium plate substrate with ruthenium-iridium coating, total effective area 1.5m²) in the electrolytic phosphating tank as the main anode, connected to the positive terminal of the electrolytic power supply; immerse four composite coated electrode plates (single electrode plate area 620cm², total effective area 0.248m²) in the circulating phosphating solution below the phosphating tank, ensuring that they do not contact the conventional inert electrode plates or the cathode substrate; arrange a 400nm ultraviolet light source at the bottom of the tank corresponding to the position of the composite coated electrode plates, with a distance of 55cm between the light source and the composite coated electrode plates and a light intensity of 10mW / cm², adjusting the angle of the light source to ensure that the light fully covers the surface of the coated electrode plates; S302. Preparation of Electrolytic Phosphating Solution and Photocatalytic Preheating: Prepare 300L of electrolytic phosphating solution according to the following formula: 1L of electrolytic phosphating solution contains 60g of industrial-grade zinc dihydrogen phosphate, 20g of industrial-grade zinc nitrate, 15mL of industrial-grade 85% phosphoric acid, 2g of industrial-grade citric acid, and the balance is industrial-grade deionized water. Pour the solution into the electrolytic phosphating tank, heat to 40℃, and maintain a stirring speed of 200r / min. Turn on the ultraviolet light source and preheat for 10min. The light transmission process is continuous and uninterrupted from the start of preheating to the end of the process. S303. Substrate pretreatment and production line connection: Connect the 6mm raw material coiled steel wire sequentially to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted take-up machine; S304. Set the electrolysis process parameters: The current density of the conventional inert energized anode is 25A / dm², the wire speed is 1.6m / s, turn on the electrolytic phosphating power supply and the inverted winding machine, and carry out continuous electrolytic phosphating treatment on the wire. For every 10 hours of continuous production, add 0.2g / L of industrial-grade citric acid to the bath solution. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire; after phosphate treatment, the wire is rinsed in a post-washing tank to remove residual solution from the surface, and then air-dried to obtain phosphated wire.
[0091] Example 5 A method for preparing cadmium sulfide nanorods includes the following steps: The raw materials, by weight percentage, include: 6% industrial-grade cadmium chloride, 4% industrial-grade thiourea, 0.5% compound morphology control agent (SDBS: dodecylpyrrolidone: TGA=1:1:1, w / w / w), industrial-grade sodium hydroxide to adjust the pH to 9.5, and the remainder is industrial-grade deionized water.
[0092] S101. Use industrial-grade deionized water as a solvent in a reaction vessel and start magnetic stirring at 300 r / min at room temperature; S102. Add 6% cadmium chloride (based on the total mass of the pre-set reaction solution) to the solvent and stir continuously for 30 minutes until completely dissolved; S103. Keep stirring, add 0.5% of the compound morphology control agent (based on the total mass of the preset reaction solution), and continue stirring for 20 minutes until completely dissolved; S104. While keeping the stirring constant, add 4% thiourea (based on the total mass of the preset reaction solution) to the mixed solution and stir for 15 minutes until completely dissolved; S105. While maintaining constant stirring, add industrial-grade sodium hydroxide solution (50% mass concentration) at a rate of 1 drop / second, and monitor the pH value in real time until it stabilizes at 9.5; S106. Add water to the preset total mass of the reaction solution with industrial-grade deionized water, and continue stirring for 5 minutes to obtain a homogeneous and transparent hydrothermal reaction solution; S107. The hydrothermal reaction solution is loaded into a polytetrafluoroethylene liner and sealed into a hydrothermal reactor. The temperature is increased to 180°C at a rate of 5°C / min, and the reaction is kept at a constant temperature for 12 hours. After the reaction is completed, the mixture is allowed to cool naturally to room temperature. S108. Transfer the reaction solution to a centrifuge and centrifuge at 10,000 r / min for 15 min. Collect the bottom precipitate and wash it 4 times with industrial-grade deionized water and 2 times with industrial-grade anhydrous ethanol. Centrifuge for 5 min after each wash. S109. The washed precipitate was placed in a vacuum drying oven at 80℃ (vacuum degree -0.1MPa) and dried for 14h, then allowed to cool naturally to room temperature to obtain cadmium sulfide nanorods.
[0093] A method for preparing a cadmium sulfide nanorod composite coated electrode based on photocatalytic effect includes the following steps: The raw materials, by weight percentage, include: 15% cadmium sulfide nanorods, 75% industrial-grade waterborne epoxy resin, 5% industrial-grade sodium polycarboxylate, 3% industrial-grade propylene glycol methyl ether, 2% industrial-grade silane coupling agent KH550, and the balance being industrial-grade deionized water; combined with a 620cm² titanium mesh inert conductor substrate.
[0094] S201. Use industrial-grade deionized water as a solvent in a reaction vessel, start stirring at 600 r / min at room temperature, add 75% water-based epoxy resin (based on the total mass of the preset composite coating liquid), and continue stirring for 40 min until completely dissolved; S202. While keeping the stirring constant, add 5% sodium polycarboxylate (based on the total mass of the preset composite coating liquid) and continue stirring for 25 minutes until completely dissolved; S203. Keeping the stirring state unchanged, add 2% KH550 (based on the total mass of the preset composite coating liquid) to the mixed solution, and stir for 20 minutes until the system is uniformly mixed; S204. Keep the stirring rate constant and add 15% cadmium sulfide nanorods (based on the total mass of the preset composite coating liquid) in 3 batches, with an interval of 5 minutes between each batch. After the addition is complete, continue stirring for 60 minutes until the nanorods are evenly dispersed. S205. Reduce the stirring speed to 300 r / min, add 3% propylene glycol methyl ether (based on the total mass of the preset composite coating liquid), and stir for 15 min until uniformly mixed; S206. Add industrial-grade deionized water to the preset total mass of the composite coating liquid, and continue stirring at 300 r / min for 5 min to obtain a uniform, bubble-free cadmium sulfide nanorod composite coating liquid. Seal and let stand for later use. S207. Select titanium mesh as the inert conductor substrate, place it in 15% industrial grade dilute hydrochloric acid, heat it in a 90℃ water bath for 40 minutes to remove oil and rust, take it out and rinse it with industrial grade deionized water until neutral, and drain the surface moisture. S208. Place the treated titanium mesh in a 70℃ forced-air drying oven for 3 hours, and cool it to room temperature before use; S209. Immerse the pretreated substrate vertically into the composite coating liquid and pull it up at a constant speed of 3 cm / min. After pulling up, place it in a ventilated place at room temperature for 15 min to pre-dry and form a semi-cured coating film. S210. Place the electrode plate with the semi-cured coating in the sandblasting equipment, use 180-mesh fine white corundum abrasive as the sandblasting medium, adjust the sandblasting pressure to 0.25MPa, and hold the sandblasting gun at a 45° angle to the coating surface. Slowly and uniformly reciprocate for 3 minutes. After sandblasting, gently rinse the coating surface with low-pressure deionized water, and then blow it dry with nitrogen. S211. Place the sandblasted activated electrode plate in a forced-air drying oven, raise the temperature to 150°C at a rate of 4°C / min, and cure at a constant temperature for 4 hours. After curing, allow it to cool naturally to room temperature. S212. Repeat S209~S211 for a second coating, with the second sandblasting pressure reduced to 0.15MPa and the sandblasting time being 2min; S213. After cooling, the electrode plate is visually inspected. The coating surface is uniform, without cracks, bubbles, or peeling, and the micro-rough structure is evenly distributed. After passing the inspection, the plate is sealed and stored to obtain the composite coated electrode plate.
[0095] An electrolytic phosphating process based on photocatalytic effect to regulate free acid includes the following steps: S301. Electrode Arrangement and Light Source Installation: Install conventional electrolytic phosphating inert electrode plates (titanium plate substrate with ruthenium-iridium coating, total effective area 1.5m²) in the electrolytic phosphating tank as the main anode, connected to the positive terminal of the electrolytic power supply; immerse four composite coated electrode plates (single electrode plate area 620cm², total effective area 0.248m²) in the circulating phosphating solution below the phosphating tank, ensuring that they do not contact the conventional inert electrode plates or the cathode substrate; arrange a 400nm ultraviolet light source at the bottom of the tank corresponding to the position of the composite coated electrode plates, with a distance of 55cm between the light source and the composite coated electrode plates and a light intensity of 10mW / cm², adjusting the angle of the light source to ensure that the light fully covers the surface of the coated electrode plates; S302. Preparation of Electrolytic Phosphating Solution and Photocatalytic Preheating: Prepare 300L of electrolytic phosphating solution according to the following formula: 1L of electrolytic phosphating solution contains 60g of industrial-grade zinc dihydrogen phosphate, 20g of industrial-grade zinc nitrate, 15mL of industrial-grade 85% phosphoric acid, 2g of industrial-grade citric acid, and the balance is industrial-grade deionized water. Pour the solution into the electrolytic phosphating tank, heat to 40℃, and maintain a stirring speed of 200r / min. Turn on the ultraviolet light source and preheat for 10min. The light transmission process should be continuous and uninterrupted from the start of preheating until the end of the process. S303. Substrate pretreatment and production line connection: Connect the 6mm raw material coiled steel wire sequentially to the straightening machine, belt sander, voltage guide roller, water washing tank, electrolytic phosphating tank, post-water washing tank, and inverted take-up machine; S304. Set the electrolysis process parameters: The current density of the conventional inert energized anode is 25A / dm², the wire speed is 1.6m / s, turn on the electrolytic phosphating power supply and the inverted winding machine, and carry out continuous electrolytic phosphating treatment on the wire. For every 10 hours of continuous production, add 0.2g / L of industrial-grade citric acid to the bath solution. S305. Film Formation and Post-treatment: A phosphate film layer of zinc phosphate and metallic zinc is formed on the cathode surface of the metal wire; after phosphate treatment, the wire is rinsed in a post-washing tank to remove residual solution from the surface, and then air-dried to obtain phosphated wire.
[0096] Comparative Example 1 In the preparation of cadmium sulfide nanorods, the composite morphology control agent was replaced with a single thioglycolic acid (TGA), with the addition amount remaining unchanged at 0.5% (weight percentage), and dodecylpyrrolidone and sodium dodecylbenzenesulfonate (SDBS) were removed.
[0097] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated electrode plates, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0098] Comparative Example 2 In the preparation of cadmium sulfide nanorods, the compound morphology control agent was replaced with a single industrial-grade sodium dodecylbenzenesulfonate (SDBS), with the addition amount remaining unchanged at 0.5% (weight percentage), and dodecylpyrrolidone and thioglycolic acid (TGA) were removed.
[0099] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated electrode plates, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0100] Comparative Example 3 In the preparation of cadmium sulfide nanorods, the compound morphology control agent is replaced with a single industrial-grade dodecylpyrrolidone, with the addition amount remaining unchanged at 0.5% (weight percentage), and sodium dodecylbenzenesulfonate (SDBS) and thioglycolic acid (TGA) are removed.
[0101] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated electrode plates, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0102] Comparative Example 4 In the preparation of cadmium sulfide nanorods, the ternary composite morphology control agent was replaced with a binary composite morphology control agent (sodium dodecylbenzenesulfonate SDBS: thioglycolic acid TGA = 1:1), while the total addition amount remained unchanged at 0.5% (weight percentage), and dodecylpyrrolidone was removed.
[0103] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated electrode plates, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0104] Comparative Example 5 In the preparation method of composite coated plates, the S10 sandblasting step is directly omitted (no sandblasting for the first coating), and the sandblasting step for the second coating is also omitted. After the titanium mesh is dip-coated, it is directly pre-dried and cured.
[0105] All other contents, including the proportions of raw materials, preparation of cadmium sulfide nanorods, remaining steps of the coated electrode, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0106] Comparative Example 6 In the electrolytic phosphating process, the 320-400nm ultraviolet light source is replaced with a 450nm visible light source. The light source spacing and light intensity remain at 55cm and 10mW / cm², respectively, and the light is continuously transmitted throughout the process.
[0107] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated plates, and other process parameters for electrolytic phosphating, are completely consistent with those in Example 3.
[0108] Comparative Example 7 In the electrolytic phosphating process, the addition of citric acid is completely eliminated from the electrolytic phosphating bath solution formula, while the remaining components (60g zinc dihydrogen phosphate, 20g zinc nitrate, 15mL / L 85% phosphoric acid) and solution preparation steps remain unchanged.
[0109] All other aspects, including the proportions of raw materials, preparation of cadmium sulfide nanorods, preparation of coated plates, and other process parameters for electrolytic phosphating, are completely consistent with those in Example 3.
[0110] Comparative Example 8 In the preparation method of the composite coated electrode plate, the curing temperature is reduced from 150℃ to 90℃, while the heating rate and the isothermal time remain at 4℃ / min and 4h, respectively. Both the first and second curing processes are adjusted accordingly.
[0111] All other contents, including the proportions of raw materials, preparation of cadmium sulfide nanorods, remaining steps of the coated electrode, and electrolytic phosphating process parameters, are completely consistent with those in Example 3.
[0112] Characterization section: The cadmium sulfide nanorods prepared in the above examples and comparative examples were characterized by electron microscopy and X-ray diffraction (XRD). The free acid content of the phosphating bath during electrolytic phosphating was also detected. Furthermore, the performance indicators of the phosphating film on the coiled steel wire after electrolytic phosphating were tested. The relevant characterization and test results are summarized below: (1) Cadmium sulfide synthesis experiments were carried out according to the synthesis parameters of each example and comparative example. The morphology of cadmium sulfide nanorods (cadmium sulfide particles) obtained in Example 3 and Comparative Examples 1-4 was examined by electron microscopy. The results are as follows: Figure 1 As shown.
[0113] pass Figure 1 The SEM images clearly show that the sample of Example 3 of this application exhibits a uniform nanorod structure at the microscale, with good particle dispersion and no obvious agglomeration. In contrast, the comparative sample shows particle accumulation and a non-nanorod morphology, indicating that the process of this application effectively improves the surface structure of the material, which is conducive to exposing more active sites and provides more room for subsequent improvement.
[0114] The cadmium sulfide nanorods (cadmium sulfide particles) obtained in Example 3 and Comparative Example 1 were characterized by X-ray diffraction (XRD), and the results are as follows: Figure 2 As shown.
[0115] The crystal structure and phase composition of the samples from Example 3 and Comparative Example 1 of this application were analyzed using X-ray diffraction. Cu Kα radiation (λ = 1.5406 Å) was used as the light source, with a scanning range of 5°–80° (2θ), a scanning step size of 0.02°, and a scanning speed of 5° / min. The phase composition of the samples was qualitatively determined by analyzing the position, intensity, and full width at half maximum (FWHM) of the characteristic diffraction peaks in the XRD patterns. Figure 2 The XRD results showed that the sample of Example 3 of this application exhibited characteristic diffraction peaks at 2θ = 24.86°, 26.52°, 28.22°, 36.62°, 43.76°, 47.82°, and 51.74°. The positions and intensities of the above diffraction peaks completely matched the standard PDF card (No. 47-1179) for hexagonal cadmium sulfide, with no impurity peaks appearing. This proves that the cadmium sulfide prepared in this application has a single hexagonal phase crystal structure, high phase purity, and good crystallinity. The samples prepared in Comparative Example 1 all showed varying degrees of diffraction peak broadening and intensity reduction, and some samples showed weak impurity peaks, indicating a decrease in crystallinity and a deterioration in phase uniformity. This confirms that the raw material ratio and preparation process of this application are the key to obtaining single hexagonal cadmium sulfide nanorods.
[0116] (2) Electrolytic phosphating tests were conducted according to the process parameters of each embodiment and comparative example. Q235 steel substrate was used for continuous electrolytic phosphating treatment for 10 hours. During this period, the total acidity and free acidity of the phosphating bath were measured every 1 hour. After the electrolytic phosphating treatment was completed (a total of 10 hours), the cadmium ion (Cd) in the phosphating bath was measured. 2+ The content of ) was determined, and the final phosphating film was tested.
[0117] The phosphating films obtained in Examples 1-5 and Comparative Examples 1-8 were tested for various performance indicators, and the test results are shown in Table 1. Metallographic analysis was performed on the phosphating films obtained in Example 3 and Comparative Examples 1-8, and the test results are shown in Table 1. Figure 3 As shown.
[0118] The specific testing methods and conditions for the performance of the phosphating film in this experiment are as follows: ① Adhesion: Tested according to GB / T 1720-2020 "Paint Film Cross-Cut Test Method"; ② Corrosion resistance: The copper sulfate pitting test method was used. The prepared pitting solution was dropped onto the sample surface and the time when red corrosion spots appeared on the surface was recorded. The pitting solution formula was: 41 g of copper sulfate pentahydrate, 35 g of sodium chloride, 13 mL of 0.1 mol / L hydrochloric acid, and distilled water was added to make up to 1 L. ③ Sodium chloride solution immersion: Immerse the phosphating sample in a 3wt% sodium chloride aqueous solution at room temperature, let it stand for the specified time, and then visually observe whether rust appears on the sample surface. ④ Indoor rust prevention: Place the dried phosphating test piece in a room temperature environment with relative humidity ≤70% and no corrosive gases, and record the time when rust appears on the test piece surface.
[0119] Table 1:
[0120] Figure 3As shown in Table 1, Examples 1-5 using the complete process of this invention all exhibited excellent film performance, with Example 3 showing the best performance. The phosphating films in all examples were dense and continuous with no pinholes or cracks, and the film thickness was within a reasonable range of 7.0~9.0μm. The adhesion all reached the highest first-class standard, the copper sulfate pitting corrosion resistance exceeded 3.5min, the immersion time in 3wt% sodium chloride solution exceeded 6h, and the indoor rust prevention time exceeded 50d. Each comparative example, due to deviations from the design at different process stages, exhibited varying degrees of film performance degradation. The degree of degradation was directly related to process defects. Comparative examples 1-4, by simplifying the ternary composite morphology control agent, resulted in cadmium sulfide with a non-uniform nanorod structure, significantly reducing photocatalytic efficiency. An imbalance in the bath acid ratio led to loose film crystals, uneven grain distribution, and varying degrees of cracking. Film thickness was also significantly reduced, adhesion dropped to level two, and corrosion and rust resistance drastically decreased. Comparative example 5 omitted the sandblasting step in coating electrode preparation, preventing the coating from forming a uniform micro-rough structure. Insufficient exposure of photocatalytic active sites resulted in decreased catalytic efficiency, loose film crystals with obvious cracks, and significantly deteriorated protective performance. Comparative example 6 replaced the ultraviolet light source with a 450nm visible light source, exceeding the effective wavelength range of cadmium sulfide photocatalysis. This caused photocatalytic failure, uncontrolled bath acid value, loose film crystals, uneven film formation, a thickness of only 2.0~3.0μm, and extremely poor corrosion resistance. Comparative example 7... The removal of citric acid sacrificial agent from the bath led to easy recombination of photogenerated electrons and holes, resulting in a significant decrease in photocatalytic hydrogen removal efficiency. The free acid in the bath also increased rapidly, leading to incomplete film formation, loose crystals, and a substantial decline in protective performance. In Comparative Example 8, the curing temperature of the coated electrode was lowered, resulting in poor adhesion and structural stability between the coating and the substrate. During prolonged production, the coating peeled off, affecting photocatalytic efficiency. The film crystallized unevenly and exhibited obvious cracks, with all performance characteristics remaining at a poor level.
[0121] The results of testing the total acidity and free acidity of the phosphating bath solution in Examples 1-5 and Comparative Examples 1-8 during the electrolytic phosphating process are shown in Tables 2 and 3.
[0122] The specific testing methods and conditions for the total acidity and free acidity of the phosphating bath solution in this experiment were conducted in accordance with GB / T 9725-2007 "General Rules for Potentiometric Titration of Chemical Reagents". Table 2: Total Acidity (Point) Detection Results
[0123] Table 3: Results of Free Acidity (Point) Detection
[0124] The results above (Tables 2 and 3) show that during the electrolytic phosphating process from 0 to 10 hours, the total acidity and free acidity of the bath solutions in all groups continuously increased with increasing reaction time, with only the magnitude of the increase differing significantly due to the varying degrees of photocatalytic effect. Examples 1-5 exhibited a slow, slight increase in acid value due to the effective photocatalytic effect, demonstrating excellent overall stability. Example 3, as the optimal process, showed the smallest increase in acid value and the best photocatalytic acid adjustment effect. The acid value changes in the other examples showed similar patterns, all maintaining good acid adjustment effects. Comparative Examples 1-8 all experienced complete photocatalytic failure or significant efficiency degradation for various reasons, resulting in a much greater increase in acid value than all examples. Specifically, Comparative Examples 1-4 yielded irregularly shaped cadmium sulfide particles with a significant decrease in photocatalytic efficiency. Comparative Example 6 suffered complete photocatalytic failure due to the light source wavelength being out of range. These five groups showed the most significant acid value increases, remaining high at 10 hours, exhibiting clear signs of acid value runaway. Comparative Examples 5, 7, and 8 experienced a decrease in photocatalytic efficiency due to process or parameter deviations, with acid value increases slightly lower than Comparative Examples 1 and 3, but still significantly higher than the examples. Overall, the effective functioning of the photocatalytic effect is crucial for maintaining stable acid value in the electrolytic phosphating bath. When the catalysis is functioning normally, it can precisely consume free H₂. + It can significantly suppress the rise in acid value, while catalytic failure or efficiency decay will cause the acid value to rise rapidly, and the stability of the bath solution will be severely damaged.
[0125] Inductively coupled plasma atomic emission spectrometry (ICP-ESO) was used to detect cadmium ions (Cd²⁺) in the phosphating baths after continuous electrolytic phosphating treatment in Examples 1-5 and Comparative Examples 1-8. + The content of cadmium sulfide nanorod composite coated plates was measured to verify their chemical stability and lack of heavy metal leaching. The test results are shown in Table 4.
[0126] Test methods and conditions: The test was conducted according to GB / T 23942-2023 "Determination of Impurity Element Content in Inorganic Chemical Products by Inductively Coupled Plasma Atomic Emission Spectrometry"; an inductively coupled plasma atomic emission spectrometer was used, with the detection spectral line selected at 226.502 nm. The instrument's lowest detection limit for cadmium ions was 0.001 mg / L. Before testing, the bath solution samples were filtered and pretreated to a fixed volume. Each sample was tested in parallel three times, and the average value was taken as the final result.
[0127] Table 4: ICP test results of cadmium ions in the bath solution after 10 hours of electrolytic phosphating
[0128] The results (Table 4) show that after electrolytic phosphating tests in all examples and comparative examples, no cadmium ions were detected in the phosphating bath of any experimental group. This indicates that under the process conditions of an acidic phosphating bath at 35-40℃, continuous ultraviolet irradiation, and bath circulation stirring, the cadmium sulfide nanorod composite coating electrode prepared by this invention did not undergo chemical dissolution of the cadmium sulfide nanorods, and no cadmium ions were released into the phosphating bath. These results confirm that the cadmium sulfide nanorod composite coating possesses excellent chemical stability and interfacial bonding. No heavy metal ions are dissolved during the entire process of photocatalytic acid adjustment and electrolytic phosphating, thus avoiding secondary pollution to the phosphating bath system and the phosphating film formation process. It also avoids the impact of heavy metal ions on the production environment and subsequent processing steps, meeting the environmental protection requirements of industrial production.
[0129] The above is a detailed description of the preferred embodiments of the present invention. However, the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention. All such equivalent modifications or substitutions are included within the scope defined by the claims of the present invention.
Claims
1. A cadmium sulfide nanorod, characterized in that, Its raw materials include: 3-6 wt% cadmium source, 1.5-4 wt% sulfur source, 0.3-0.5 wt% compound morphology control agent, pH adjuster to adjust pH to 9-9.5, and the remainder is water; The compound morphology control agent includes anionic surfactant, dodecylpyrrolidone, and mercaptocarboxylic acid; the anionic surfactant includes one or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and sodium dodecyl sulfonate; and the mercaptocarboxylic acid includes one or two of thioglycolic acid and mercaptopropionic acid. The preparation method of the cadmium sulfide nanorods includes the following steps: After mixing cadmium source, sulfur source, compound morphology control agent, pH adjuster and water, hydrothermal reaction was carried out, followed by centrifugation, washing and drying to obtain cadmium sulfide nanorods; the hydrothermal reaction temperature was 160-180℃, and the reaction was carried out at a constant temperature for 6-12 hours.
2. The cadmium sulfide nanorods according to claim 1, characterized in that, The mass ratio of the anionic surfactant, dodecylpyrrolidone, and mercaptocarboxylic acid is (1-2):(1-2):1; The cadmium source includes one or more of cadmium nitrate, cadmium acetate, cadmium chloride, and cadmium sulfate; The sulfur source includes one or more of sodium thiosulfate, thiourea, sodium sulfite, and sodium sulfide; The pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, ammonium bicarbonate, and triethanolamine.
3. The method for preparing cadmium sulfide nanorods according to any one of claims 1-2, characterized in that, Includes the following steps: After mixing cadmium source, sulfur source, compound morphology control agent, pH adjuster and water, hydrothermal reaction was carried out, followed by centrifugation, washing and drying to obtain cadmium sulfide nanorods; the hydrothermal reaction temperature was 160-180℃, and the reaction was carried out at a constant temperature for 6-12 hours.
4. The method for preparing cadmium sulfide nanorods according to claim 3, characterized in that, Under stirring, the cadmium source, compound morphology control agent, sulfur source and pH adjuster are added to the water in sequence and mixed. The stirring rate is 300-500 r / min; The centrifugation speed is 8000-10000 r / min, and the time is 10-15 min; The washing process involves water and ethanol. The drying process is vacuum drying, with a temperature of 60-80℃, a vacuum degree of (-0.08)~(-0.1)MPa, and a time of 12-14h.
5. A cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect, characterized in that, The composite coating comprises a substrate and a composite coating. The raw materials for the composite coating include the following components by weight percentage: The cadmium sulfide nanorods according to any one of claims 1-2 or the cadmium sulfide nanorods prepared by the preparation method according to any one of claims 3-4 contain 8%-15% cadmium sulfide nanorods, 70%-75% binder, 2%-5% dispersant, 1%-3% film-forming aid, 0.5%-2% coupling agent, and the balance being water.
6. The cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect according to claim 5, characterized in that, The substrate is an inert conductor substrate; The adhesive aid includes one or more of waterborne epoxy resin, waterborne polyurethane, and acrylate adhesive; The dispersant includes one or more of sodium polycarboxylate, sodium hexametaphosphate, and polyvinylpyrrolidone; The film-forming aid includes one or more of propylene glycol methyl ether, ethylene glycol butyl ether, and dodecyl alcohol ester; The coupling agent includes one or more of the following: silane coupling agents KH550 and KH560, and titanate coupling agents.
7. The method for preparing the cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect according to any one of claims 5-6, characterized in that, Includes the following steps: After mixing the adhesive, dispersant, coupling agent, cadmium sulfide nanorods, film-forming aid and water, a composite coating liquid is obtained. The substrate is first immersed in the composite coating liquid, then removed, dried, sandblasted and cured. Then it is immersed in the composite coating liquid a second time, removed, dried, sandblasted and cured to obtain a cadmium sulfide nanorod composite coating electrode plate based on photocatalytic effect.
8. The method for preparing the cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect according to claim 7, characterized in that, Under stirring, the thickener, dispersant, coupling agent, cadmium sulfide nanorods and film-forming aid are added to the water in sequence and mixed. The substrate is an inert conductor substrate; The substrate has undergone degreasing and rust removal treatment; The degreasing and rust removal process involves heating the substrate in a water bath with hydrochloric acid. The concentration of the hydrochloric acid is 10%~15%, and the water bath heating temperature is 80~90℃ for 30~40 minutes; During the first impregnation of the composite coating liquid, including removal, drying, sandblasting, and curing, the substrate is vertically immersed in the composite coating liquid and pulled up at a constant speed of 2-3 cm / min. Drying is carried out at room temperature with ventilation for 10-15 minutes. Sandblasting uses 120-180 mesh fine white corundum abrasive as the blasting medium, with the blasting pressure adjusted to 0.15-0.25 MPa. The blasting gun is held at a 30°-45° angle to the coating surface, and blasting is performed in a reciprocating motion for 2-3 minutes. The curing temperature is 120-150℃, and the time is 2-4 hours. During the second impregnation of the composite coating liquid, including removal, drying, sandblasting, and curing, the substrate is vertically immersed in the composite coating liquid and pulled up at a constant speed of 2-3 cm / min. Drying is carried out at room temperature with ventilation for 10-15 minutes. Sandblasting uses 120-180 mesh fine white corundum abrasive as the sandblasting medium, with the sandblasting pressure adjusted to 0.1-0.15 MPa. The sandblasting gun is at a 30°-45° angle to the coating surface, and sandblasting is performed in a reciprocating manner for 1-2 minutes. The curing temperature is 120-150℃, and the time is 2-4 hours.
9. The method for preparing the cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect according to claim 8, characterized in that, The substrate is a titanium mesh.
10. An electrolytic phosphating process based on photocatalytic effect to regulate free acid, characterized in that, Includes the following steps: Electrolytic phosphating is performed using an inert electrode plate as the anode, the workpiece to be phosphated as the cathode, and an electrolytic phosphating solution containing a sacrificial agent as the electrolyte. During the electrolytic phosphating process, the cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect as described in any one of claims 5-6, or the cadmium sulfide nanorod composite coated electrode plate based on photocatalytic effect prepared by the preparation method described in any one of claims 7-9, is placed in the electrolytic phosphating solution containing a sacrificial agent for ultraviolet light irradiation.
11. The electrolytic phosphating process based on photocatalytic effect to regulate free acid according to claim 10, characterized in that, The wavelength of the ultraviolet light is 320-400nm; The sacrificial agent is one or more of alcohols, organic acids, and thiosulfates; The sacrificial agent is one or more of triethanolamine, citric acid, sodium thiosulfate, and potassium thiosulfate; The sacrificial agent-containing electrolytic phosphating solution comprises: 60-80 g / L zinc dihydrogen phosphate, 20-40 g / L zinc nitrate, 15-30 mL / L 85% phosphoric acid, 3-5 g / L sacrificial agent, and the balance being water; The stirring rate for the electrolytic phosphating is 100~200 r / min, and the temperature is 35~40℃; Sacrificial agents are added at intervals during the electrolytic phosphating process.
Citation Information
Patent Citations
Method for preparing cadmium sulfide nanorod by taking two-dimensional layered material as template and product
CN103011259A
Preparation method of mixed crystal phase heterojunction nano-cadmium sulfide with special morphology
CN107138167A
